Mapping of behavioural quantitative trait loci - Turri, M (2002)
﻿ Anxiety is a common disorder which affects about 25% of the population and whose pathophysiology is still poorly understood. Animal models of disease have been widely used to investigate the molecular basis of human disorders, including psychiatric illnesses. This thesis is about the study of the genetic basis of a mouse model of anxiety. I have carried out a QTL mapping study of behavioural measures thought to model anxiety. I report results from 1,636 mice, assessed for a large number of phenotypes in five ethological tests. Mice belonged to two F2 intercrosses originated by four lines generated in a replicate selection experiment. By comparing mapping results between the two crosses, I have demonstrated that selection operated on the same relatively small number of loci in the four selected lines. Analysis of genetic effect of QTL across phenotypes has allowed me to identify loci with specific roles on different dimensions of anxious behaviour, therefore enhancing our understanding of the anxiety phenotype in mice. For some of these QTL I have also accomplished fine mapping experiments: a locus on chromosome 15 is now contained in an interval of only 3 centimorgans. This work is the basis for further molecular dissection of the genetic loci that underlie anxiety and provides a starting point for the discovery of genes involved in a common psychiatric condition.